2020
DOI: 10.1101/2020.05.12.091215
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synergistic neural integration is greater downstream of recurrent information flow in organotypic cortical cultures

Abstract: Cortical information processing requires synergistic integration of input. Understanding the determinants of synergistic integration-a form of computation-in cortical circuits is therefore a critical step in understanding the functional principles underlying cortical information processing. We established previously that synergistic integration varies directly with the strength of feedforward connectivity. What relationship recurrent and feedback connectivity have with synergistic integration remains unknown. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 100 publications
(151 reference statements)
0
1
0
Order By: Relevance
“…The synchronization of neuronal circuits is related to higher-order processing (Vinck et al 2015) especially in thalamic and cortical circuits. Moreover, Sherrill et al (2021) recently have shown that recurrent information flow in cortical circuits leads to an increase in neural synergy and neural complexity. Sherrill et al (2020) show that correlated activity and neural synergy were positively related when multiple external correlated stimuli are provided.…”
Section: Neural Dependency Coding In Multisensory Processingmentioning
confidence: 99%
“…The synchronization of neuronal circuits is related to higher-order processing (Vinck et al 2015) especially in thalamic and cortical circuits. Moreover, Sherrill et al (2021) recently have shown that recurrent information flow in cortical circuits leads to an increase in neural synergy and neural complexity. Sherrill et al (2020) show that correlated activity and neural synergy were positively related when multiple external correlated stimuli are provided.…”
Section: Neural Dependency Coding In Multisensory Processingmentioning
confidence: 99%